O texto dissertativo-argumentativo na escola básica: contribuições da Análise Textual dos Discursos e das metodologias ativas para o ensino da escrita - Rocha, Débora Ferreira da (2023)
This thesis has as its theme the teaching of argumentative-dissertation text in elementary school, delimited to the 9th grade of elementary school. We justify the choice by the difficulties that, as a teacher, we observe in the production of the mentioned text by most of the students who complete this stage of formation. The study, carried out in a municipal school in the city of São Paulo, is guided by two hypotheses: 1) The difficulties in writing the dissertation-argumentative text are due to the students' lack of knowledge about the construction of the argumentative textual sequence, in their propositions: assertion, support/support/conclusion and 2) The use of active methodologies in proposing rewriting activities based on studies of Textual Analysis of Discourses can enable the construction of a guiding didactic sequence for the teacher's work in facing the challenges of writing your students. The research questions that guide this research are: 1) What are the difficulties that the students of the 9th grade of elementary school who participate in the present study have in the construction of the argumentative sequence in dissertation-argumentative texts? and 2) How can the use of active methodologies in proposing rewriting activities based on studies of Textual Analysis of Discourses enable the construction of a guiding didactic sequence for the teacher's work in facing the writing challenges of their students? We have, then, as a general objective: to investigate the difficulties that students of the 9th grade of elementary school in a municipal school in São Paulo have in writing the dissertation-argumentative text and to propose a didactic sequence for dealing with the issue. The specific objectives are: (1) to identify, analyze and interpret the difficulties in constructing the argumentative textual sequence in essays produced by these students and (2) to propose a didactic sequence, based on principles of Textual Analysis of Discourses, through methodologies activities, so that students overcome the difficulties presented. Theoretically, this work is based on studies in the field of Textual Linguistics (CAVALCANTE et al., 2010; GOMES-SANTOS et al., 2010; KOCH, 2015; 2020; MARQUESI, 2004), in the approach of Textual Analysis of Discourses (ADAM, 2011; 2019; MARQUESI, 2017; PASSEGGI et al., 2010), in particular, about the text plane and textual sequences (ADAM, 2011; 2019; BENTES; MARIANO; FERREIRASILVA, 2013; BONINI, 2006; CABRAL, 2013; MARQUESI, 2004; 2011; 2018; MARQUESI; ELIAS; CABRAL, 2017; MARQUESI et al., 2019; PASSEGGI et al., 2010; SOUSA, 2007). We also make use of studies on text and on the argumentative dimension (AMOSSY, 2011; CAVALCANTE et al., 2022; FIORIN, 2015) and on active methodologies (ALVES; MINHO; DINIZ, 2014; ARAUJO, 2015; ARAUJO; MAZUR, 2013; BERGMANN; SAMS, 2021; LOVATO et al., 2018; MARQUESI; SILVEIRA, 2015; MARTINS; GIRAFFA, 2015; MATTAR, 2017; MEDEIROS, 2005; MENEZES; BORTOLI, 2018; MESQUITA, 2010; MORAN, 2018; MORAN, s.d.; MÖRSCHBÄCHER; PADILHA, 2018; PEREIRA, 2017; PEREIRA et al., 2009; RAGUZE; SILVA, 2016; SGANDERLA; CARVALHO, 2008; TOLOMEI, 2017; VALENTE, 2018). The corpus is composed of ten compositions, selected among thirty texts produced by 9th grade students. The obtained results show that the didactic sequence and the active methodologies, allied to the concepts of text plan and textual sequences, can help the student to overcome the difficulties of writing the dissertation-argumentative text